NILAI-NILAI MULTIKULTUR DALAM ANTOLOGI CERITA RAKYAT SINGKAWANG - Binar Kurniasari Febrianti (Balai Bahasa Kalimantan Barat, 2021)
This paper aims to describe multicultural values in Singkawang folklore. Singkawang folklore anthology, which reveal past socio-cultural life inherited from generation to another generation, underlies the paper. Folklore tells things related to natural phenomena, the social life of the community, and customs of origin. This paper is descriptive analysis with a literature study method and uses the theory of sociology of literature. The data source of this paper is Singkawang folklore text by applying the technique of reading and writing. The results showed that Singkawang folklore contained multicultural values, including tolerance values, equality values, religious values, cultural values, solidarity values, trade values, family values, simplicity, unyielding values, values of appreciation, and values of keeping promises. These multicultural values are still relevant and applied today. Thus, Singkawang folklore shows cultural diversity that is important as a socio-cultural reality.